THE EFFECT OF MICROCREDIT ON RURAL HOUSEHOLD LIVELIHOOD: EVIDENCES FROM WOMEN MICRO ENTREPRENEURS IN OYO STATE, NIGERIA - Clementina Oluwafunke AJAYI (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Microcredit has been found to be an intervention to improve the livelihood of women micro entrepreneurs in developing countries. It is often used as an attractive strategy to enhance the livelihoods of women as it provides micro entrepreneurs with the avenue to generate more income. The study focused on the effect of micro credit on rural households’ livelihood: evidences from women micro entrepreneurs in Oyo State, Nigeria. A descriptive survey design was adopted and 180 beneficiaries of microcredit were used. The result of the study revealed that microcredit had a positive effect on household income and welfare which led to improvement in the standard of living and opportunity to save money. The women micro entrepreneurs were able to contribute significantly to their children’s education improve the quality of meals intake and employment and housing conditions of their households. The microcredit scheme also contributed to beneficiaries’ development, sustainability and local governance participation. Above all, the respondents felt empowered. It is therefore concluded that those concerned with availing funds in form of microcredit and microfinance in general should take into consideration the results of these indicator variables for better livelihood of rural households.